2012
DOI: 10.1115/1.4003832
|View full text |Cite
|
Sign up to set email alerts
|

Hot Streak and Vane Coolant Migration in a Downstream Rotor

Abstract: This paper describes a method of improving the cooling of the hub region of highpressure turbine (HPT) rotor by making better use of the unsteady coolant flows originating from the upstream vane. The study was performed computationally on an engine HPT stage with representative inlet hot streak and vane coolant conditions. An experimental validation study of hot streak migration was undertaken on two low-speed test facilities. The unsteady mechanisms that transport hot and cold fluid within the rotor hub regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The hot streak migrates downstream and through the vane passage, causing a 12 local increase in the adiabatic vane surface temperatures near the hot streak core. The hot streak remains coherent through the passage until the exit plane, in agreement with [17] and [19]. Figure 5 shows the hot streak migration through the vane passage for the first clocking position.…”
Section: A Solutionsupporting
confidence: 72%
See 1 more Smart Citation
“…The hot streak migrates downstream and through the vane passage, causing a 12 local increase in the adiabatic vane surface temperatures near the hot streak core. The hot streak remains coherent through the passage until the exit plane, in agreement with [17] and [19]. Figure 5 shows the hot streak migration through the vane passage for the first clocking position.…”
Section: A Solutionsupporting
confidence: 72%
“…Povey et al [18] numerically and experimentally studied how the hot streak affected heat transfer on turbine vanes. Ong and Miller [19] numerically studied the migration of the combustor hot streak through a vane and rotor passage and suggested cooling schemes to improve component cooling. The circumferential size of the hot streak and its effects were analyzed be He et al [20].…”
Section: Figure 1 -Volcanic Ash Deposition On Turbine Vanesmentioning
confidence: 99%
“…These results, obtained by simulation and also confirmed experimentally, reinforce the importance of understanding the behaviour of the fluid entering the vanes. Ong and Miller [26] numerically examined the effect of hot streaks in a turbine in which hot streaks were aligned with half of the vanes in an alternating fashion by solving the URANS equations and a mixing length model. They reported that the hot streaks enhanced the secondary flows in the rotor domain and caused an increase of the temperature on the blade pressure side.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hot streaks amongst other non-uniformities cause varying thermal stresses on turbine blades. These hot streaks are responsible for enhancing the secondary flows in the rotor domain and cause an increase of the temperature on the blade pressure side [14]. Authors [1] studied the effects of six hot streak circumferential positions relative to vane leading edge in a single-stage subsonic high-pressure turbine with 40 vanes and 82 blades and observed that surface pressure fluctuations on the rotor blade for the non-uniform total inlet temperature cases were increased as compared with the uniform case.…”
Section: Introductionmentioning
confidence: 98%